Hang Tuah in the Sea of Oral Malay Narratives (Malay Literature, 2012)
Hang Tuah is a culture hero who defines both himself and the Malays, along with their feudal and universal values. Three forms of existences have been bestowed on him by the peoples of the Malay Archipelago, i. e. the historical, the fictional and the oral. This paper attempts to trace the oral presence of Hang Tuah which is more varied, colourful, and in effect, more developed than the other two. At present, in Sungai Duyung, Singkep, Riau, Malacca and many places in the Archipelago, there is a wealth of stories about him, his origins, exploits, comrades and death. Many stories of the Sea Sekanaq of West Singkep, Riau claim that he originated from amongst their people. In Bintan, however, where his family found a home, some other famous stories are told of how he met his four friends, and his early relationship with the Bendahara and the Raja of Bintan. Hang Tuah and his family moved to Malacca when the new state became an important and wealthy port. Here, the stories refer to the village of Sungai Duyong in Malacca, its famous well, and his so-called mausoleum in Tanjong Keling. Stories of his life and contribution to the state were composed over time, and are quite different from addition to those of the Sulalat al-Salatin and the Hikayat Hang Tuah. The stories are still being composed and spread through the internet, an instrument of what I call the tertiary orality.Keywords: Hang Tuah, Malay identity, feudal values, origins, orang laut